Risk Factors for Surgical Failure and Worsening Pelvic Floor Symptoms Within 5 Years After Vaginal Prolapse Repair. Issue 5 (November 2020) - Jakus-Waldman, Sharon; Brubaker, Linda; Jelovsek, John Eric; Schaffer, Joseph I.; Ellington, David R.; Mazloomdoost, Donna; Whitworth, Ryan; Gantz, Marie G.
Abstract : OBJECTIVE: To assess independent risk factors for surgical failure and worsening pelvic floor symptoms within 5 years after vaginal prolapse surgery. METHODS: This secondary analysis includes OPTIMAL (Operations and Pelvic Muscle Training in the Management of Apical Support Loss) (n=374) and E-OPTIMAL (Extended) (n=285) trial participants. Surgical failure was defined as apical descent greater than one third of the total vaginal length, anterior or posterior vaginal wall past the hymen, subsequent surgery or bothersome vaginal bulge. Worsening pelvic floor symptoms were defined as increases from baseline as large as the minimally important difference for subscale scores of the Pelvic Floor Distress Inventory: 11 for the Urinary Distress Inventory and Colorectal-Anal Distress Inventory and 34.3 for the Pelvic Organ Prolapse Distress Inventory. Outcomes were measured at 6 months then 1, 2, 3, 4, and 5 years. Chi-square and t test results from bivariate models and clinical relevance were used to inform final models. RESULTS: Baseline risk factors for surgical failure were Hispanic ethnicity (adjusted odds ratio [aOR] 1.92, 95% CI 1.17–3.15), perineal body (aOR 1.34, 95% CI 1.09–1.63), and pretreatment Pelvic Organ Prolapse Distress Inventory score (aOR 1.16, 95% CI 1.05–1.28). Risk factors for worsening of pelvic floor symptoms were pretreatment Pelvic Organ Prolapse Distress Inventory score (aOR 0.75, 95% CI 0.60–0.94) for worsening Pelvic Organ Prolapse Distress Inventory score, vaginal deliveries (aOR 1.26, 95% CI 1.10–1.44) and pretreatment Urinary Distress Inventory score (aOR 0.86, 95% CI 0.80–0.93) for worsening Urinary Distress Inventory score, and age (aOR 1.03, 95% CI 1.01–1.05) and pretreatment Colorectal-Anal Distress Inventory score (aOR 0.95, 95% CI 0.92–0.98) for worsening Colorectal-Anal Distress Inventory score. CONCLUSIONS: Hispanic ethnicity, larger preoperative perineal body, and higher pretreatment Pelvic Organ Prolapse Distress Inventory scores were risk factors for surgical failure up to 5 years after vaginal prolapse repair. Participants with higher baseline Pelvic Floor Distress Inventory scores were less likely to worsen. Risk factors for worsening Urinary Distress Inventory and Colorectal-Anal Distress Inventory scores included more vaginal deliveries and increased age, respectively. CLINICAL TRIAL REGISTRATION: NCT00597935, NCT01166373. Abstract : Surgical failure after vaginal prolapse reconstruction is associated with several baseline factors: more bothersome symptoms, longer perineal body, and Hispanic ethnicity.